Knowledge, attitude and perception of antiplatelet therapy among dentists in Central Eastern Turkey - Can, Mehmet M (Baishideng Publishing Group Co., Limited, 2012)
AIM: To survey the dentists in Central Eastern Turkey, testing their knowledge on coronary interventions and assessing perception of antecedent dual antiplatelet therapy. METHODS: Two hundred and ninety-eight dentists were surveyed face-to-face by completing questionnaires, including 16 structured questions focused on general knowledge of coronary stents, and assessing periprocedural practice with regard to antiplatelet therapy. RESULTS: All respondents were aware of such devices as coronary stents, but only one-third of the respondents knew the differences between a bare metal and a drug-eluting stent design, and associated vascular outcomes. Awareness about stent thrombosis was limited to 34%, while consequences of interrupting antiplatelet therapy were known to only 30% of surveyed dentists. Importantly, the attitudes of surveyed respondents differed substantially depending on the location of their practice, where dentists working in the urban environment (population over 10 000) were more aware of antiplatelet recommendations when compared to their colleagues from the rural areas. CONCLUSION: Knowledge about coronary stents, associated clinical outcomes, and current guidelines with regard to surgical management of antecedent antiplatelet therapy in Central Eastern Turkey is inconsistent, and heavily dependent on the location of dental practice. Rural areas around the globe should be in a focus of continuous medical education to improve the quality of medical care.